2012
DOI: 10.7314/apjcp.2012.13.4.1419
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use among Cancer Patients at the End of Life: Korean National Study

Abstract: Objectives: To investigate in depth the use of complementary and alternative medicines (CAMs) by cancer patients at the end-of-life (EOL) and how they communicate with physicians about them. Design and location: In 17 hospitals in Korea between January and December 2004 we identified 4,042 families of cancer patients. Results: The prevalence of CAM use among cancer patients at the EOL was 37.0%, and 93.1% had used pharmacologic types of agents. The most frequent motive for CAM use was the recommendation of fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Nonetheless, CAM is attracting a significant level of interest from cancer patients due to the psychological support it provides. According to previous studies, the most frequently used form of CAM is herbs (Samur et al, 2001; Molassiotis et al, 2005;Er et al, 2008;Choi et al, 2012;Saibul et al, 2012;Nazik et al, 2012). Cancer patients are thought to employ CAM to increase physical strength, restrain cancer growth, enhance the immune system, and alleviate symptoms (Hyodo et al, 2005;Molassiotis et al, 2005;Molassiotis et al, 2006;Er et al, 2008;Shin et al, 2009;Saibul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, CAM is attracting a significant level of interest from cancer patients due to the psychological support it provides. According to previous studies, the most frequently used form of CAM is herbs (Samur et al, 2001; Molassiotis et al, 2005;Er et al, 2008;Choi et al, 2012;Saibul et al, 2012;Nazik et al, 2012). Cancer patients are thought to employ CAM to increase physical strength, restrain cancer growth, enhance the immune system, and alleviate symptoms (Hyodo et al, 2005;Molassiotis et al, 2005;Molassiotis et al, 2006;Er et al, 2008;Shin et al, 2009;Saibul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…9 International studies confirm the increased use of alternative medicine among cancer patients worldwide. 8,29,31,33 This use is also often not disclosed to treating oncologists, in part due to discordant beliefs of patients and healthcare providers regarding the benefits of supplements. 34 Gender differences may be partially responsible for the differences between prostate and breast cancer patients in reported use of supplements.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Despite the unclear benefits of supplements, use tends to increase after a cancer diagnosis. 8,9,31 In 1998, Ernst and Cassileth reported a systematic review of 26 studies evaluating complementary alternative medicine (CAM) use in cancer patients, and they found that 40% of patients reported alternative medicine use. This review was limited as each individual study defined CAM differently, including both nonpharmacologic treatments and dietary supplements.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, overall reasons for taking CAMs have included strengthening the immune system, improving emotional or physical well-being, improving the body's capacity to perform daily activities, 11,29,31 reducing psychological stress and physical symptoms, and gaining a feeling of control over treatment, but a distinctive pattern for specific CAM types and specific reasons was not clearly apparent. 32,33 In terms of satisfaction, most users were satisfied with perceived benefits of CAM, 29,32 but lack of improvement in expected goal was the most common reason for dissatisfaction.…”
Section: Prevalence and Types Of Cam Usedmentioning
confidence: 99%
“…32,33 In terms of satisfaction, most users were satisfied with perceived benefits of CAM, 29,32 but lack of improvement in expected goal was the most common reason for dissatisfaction. 31 …”
Section: Prevalence and Types Of Cam Usedmentioning
confidence: 99%